PRIMUS INTER PARES Review of the new monograph by Prof. E.T. Usenko “Essays of the International Law Theory” (M.: Norma, 2008. 239 p.) - L. P. Anufrieva (Московский журнал международного права, 2008)
The main asset of the book is first of all that it managed to include all its author’s major scientific achievements made in different areas of the contemporary international law, which according to his own opinion require further fundamental studies and deeper knowledge. Among these fields of international law theory the most important are the following issues: essence of international law conceived as integral system; legal personality of international (intergovernmental) organizations; relationship between international law and private international law; evolution and the periodization of the history of international law theory; system of the contemporary international law; theoretical issues of relationship between the international and municipal law; relationship and inter-action between international and national law with regard to the Constitution of Russia; acute problems of the so-called “extraterritorial effect” of the expatriate laws; the Decree of Peace – the international legal Declaration of the October Revolution; non-violent peace – the fundamental principle and target of contemporary international law. The list of issues mentioned above reflects the structure and composition of the book, which consists of 11 essays. The main part of the monograph is the author’s solution to the problem of the system of international law that represents the theory developed by E.T. Usenko in his earlier publications.In the frameworks of the short book-review, it is hard indeed to give an overwhelming analysis of the work. Still it will not be an exaggeration to say that a profound study of the “Essays on the Theory of International Law” from the point of view of ideas, conclusions and statements contained therein would certainly be of vital interest for scholars within a long time in the forthcoming future.